2020
DOI: 10.1039/d0pp00117a
|View full text |Cite
|
Sign up to set email alerts
|

Tips and turns of bacteriophytochrome photoactivation

Abstract: Phytochromes are red light-sensing photoreceptors. Here we review the current understanding of phytochrome photoactivation, with a special focus on bacteriophytochromes and their crystallographic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 177 publications
(251 reference statements)
3
59
0
Order By: Relevance
“…In particular, we have shown that the connection between the conformation of the chromophore and the following largescale changes in the secondary and tertiary structure of the PSM is not univocal thus allowing the phytochrome to exploit redundant routes for its activation. 17,18…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, we have shown that the connection between the conformation of the chromophore and the following largescale changes in the secondary and tertiary structure of the PSM is not univocal thus allowing the phytochrome to exploit redundant routes for its activation. 17,18…”
Section: Resultsmentioning
confidence: 99%
“…We conclude this analysis by recalling that a single-point mutation of the conserved Tyr263 residue resulted in a decoupling between the chromophore state and the conformation of the PSM. 17,18 In fact, the Y263F mutant PSM could adopt a Pfrlike overall structure and a a-helix conformation for the tongue, with the chromophore in the Pr state. These experimental results suggest that the entire opening mechanism of the PSM is controlled by the tongue conformation, and not by the chromophore directly.…”
Section: Structural Changes In the Photosensory Modulementioning
confidence: 99%
See 1 more Smart Citation
“…The prototypical BphP architecture consists of an N-terminal photosensory module (PSM), which autocatalytically binds biliverdin IXα (BV) chromophore to a conserved cysteine residue, and a C-terminal variable output module (OM), responsible for transducing the PSM light-driven conformational changes into a specific physiological signal ( 59 ).…”
Section: Introductionmentioning
confidence: 99%
“…BphPs usually show a dimeric quaternary structure, where monomers are docked to each other in a parallel or antiparallel arrangement through long helical bundles across the different domains called GAF-PHY and PHY-OM helical linkers, which form the “helical spine” ( 6 , 7 ). Other outstanding structural features from these photoreceptors are (i) the presence of a figure-of-eight knot that crosses over residues between the PAS and GAF domains, strengthening their association ( 10 ), and (ii) a highly conserved hairpin protrusion from the PHY domain, termed as the “tongue”, which encloses the chromophore binding pocket by interacting electrostatically with the GAF domain ( 69 ).…”
Section: Introductionmentioning
confidence: 99%